MARKETING MANAGEMENT OF THE QUALITY OF DIGITAL PRODUCTS IN THE SPHERE OF INFORMATION SERVICES AT THE STAGE OF DEVELOPMENT OF INDUSTRY 5.0 - TELNOV Anatolіі; RESHMIDILOVA, Svitlana; KULATSKY, Vadym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is to substantiate the concept of marketing management of the quality of digital products in the field of information services, taking into account the main trends in the development of Industry 5.0. The article justifies the transition from Industry 4.0 and identifies the main trends in the development of Industry 5.0. The features of Industry 5.0 that are important in the field of information services are highlighted. The need to improve the quality of digital products in the field of information services is argued to ensure their competitiveness in the market. The need for marketing management of the quality of digital products in the field of information services as a tool for meeting user expectations is determined. The path of creating a digital product, indicators and methods for assessing its quality are characterized, and the marketing tools used are analyzed using the example of the Stfalcon company. Automated testing of digital products is analyzed. The conclusion is made about the need for competitor analysis and the development of a prototype of a digital product for its validation and testing before implementation.Marketing quality management of digital products with its research tools and quality assessment allows you to ensure that the product meets the needs of users. The implementation of the discovery phase is the basis for creating a quality digital product that meets the needs of users and ensures the creation of a competitive product that stands out among other competitors.